2015
DOI: 10.1590/0102-311x00180613
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de vida e AIDS sob a ótica de pessoas vivendo com o agravo: contribuição preliminar da abordagem estrutural das representações sociais

Abstract: Trata-se de estudo descritivo, qualitativo, tendo por objetivos: identificar o conteúdo e a estrutura das representações sociais da qualidade de vida e da AIDS entre pessoas com a doença e analisar as relações estruturais entre tais representações. Os sujeitos foram 103 pessoas soropositivas de município norte fluminense, Brasil. Empregou-se técnica de evocação livre e hierarquizada de palavras aos termos indutores "AIDS" e "qualidade de vida da pessoa que tem AIDS", com análise pelo software EVOC. Foram ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
22

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 13 publications
2
20
0
22
Order By: Relevance
“…This is because the three basic components of a representation were identified and form the representational field, the formulation of knowledge on the object, and the favourable or unfavourable positioning of the group (attitude) (12)(13)(14)(15) . Other studies identified the connection between the nursing profession and caring/care, especially among nursing professionals, users of health services approached in the doctor's waiting rooms in healthcare units, and HIV-positive patients (14)(15)(16) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is because the three basic components of a representation were identified and form the representational field, the formulation of knowledge on the object, and the favourable or unfavourable positioning of the group (attitude) (12)(13)(14)(15) . Other studies identified the connection between the nursing profession and caring/care, especially among nursing professionals, users of health services approached in the doctor's waiting rooms in healthcare units, and HIV-positive patients (14)(15)(16) .…”
Section: Discussionmentioning
confidence: 99%
“…Next, we used EVOC 2003 -Ensemble des programmes permettant l' analyse des evocations. This software calculates and notifies the simple frequency of occurrence, the average frequency of occurrence of each word in the order of evocation, and weighted average of the average order of evocation (AOE) of the set of terms (10)(11)(12) . The data were presented using a four-box table containing the average frequency and order of the evocations.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Os resultados revelam que as concepções sobre a aids estão relacionadas aos aspectos da vivência da soropositividade, focando nos âmbitos sociais de isolamento e de cuidados referentes ao diagnóstico da aids, sendo os termos centrais identificados pelos conceitos Preconceito, Doença e Tratamento, que são similares a outros estudos (Costa, Oliveira, & Formozo, 2015;Natividade & Camargo, 2011). Desta forma, os dados apresentados apontam uma ambivalência entre os conhecimentos sobre a aids.…”
Section: Discussionunclassified